Radiolabeling and In-Silico Study of 131I-(4-fluorobenzoyl-3-methylthiourea) as Radiopharmaceuticals for Breast Cancer Theranostics - Pratama, Febby; Ruswanto, Ruswanto; Nofianti, Tita; Pratita, Anindita Tri Kusuma; Daruwati, Isti; Susilo, Veronika Yulianti; Holik, Holis Abdul (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2024)
The chemicals produced from thiourea are actively being studied as anticancer possibilities. In complexes with radionuclides like Iodine-131, the 1-(4-Fluorobenzoyl)-3-methyl thiourea is a promising ligand for theragnostic applications. This study aimed to label 1-(4-fluorobenzoyl-3-methylthiourea) with iodine-131 and observe its interaction with breast cancer receptors. The radiolabeling of 131I-(4-fluorobenzoyl-3-methylthiourea) uses the radioiodination method with Chloramine-T, and an in-silico investigation of breast cancer receptors was conducted. According to the results of molecular docking using AutoDockTools, this radiopharmaceutical molecule has the best activity on the HER2 receptor (PDB ID: 3PP0) compared to the native ligand and control positive, with a binding affinity of -6.13 kcal/mol and a Ki value of 32.05 mM. According to the molecular dynamics data using Desmond, the radiopharmaceutical molecule 131I-(4-Fluorobenzoyl-3-methylthiourea) displays good stability starting from the 50ns range. The indirect radioiodination method has successfully labeled 1-(4-Fluorobenzoyl-3-methylthiourea) with iodine-131.